Angiography-guided Multivessel Percutaneous Coronary Intervention Versus Ischemia-guided Percutaneous Coronary Intervention Versus Medical Therapy in the Management of Significant Disease in Non–Infarct-related Arteries in ST-Elevation Myocardial Infarction Patients With Multivessel Coronary Disease. Issue 2 (June 2018) - Perera, Dhanuka; Crake, Tom; Lee, Victor
Abstract : Background: In ST-elevation myocardial infarction (STEMI) patients with multivessel (MV) disease, after primary percutaneous coronary intervention (PCI), emerging evidence suggests that significant disease in non–infarct-related coronary arteries (IRAs) should be routinely stented. Whether this procedure should be guided by angiography alone or ischemia testing is unclear. Methods: All STEMI patients treated with primary PCI between January 1, 2005, and December 31, 2012, at a tertiary cardiology center were reviewed retrospectively. Inclusion criterion is patients with at least 70% stenosis in non-IRAs. There were 3 treatment groups: (1) angiography-guided MV-PCI, (2) ischemia-guided PCI, and (3) medical therapy. Primary endpoint is all-cause mortality, and secondary end point is major adverse cardiovascular events (MACE), including death, acute coronary syndrome, revascularization, or stent thrombosis. Event-free survivals were compared using multivariate Cox proportional-hazards analysis. A propensity score–adjusted analysis was performed. Results: Four hundred forty-seven STEMI patients had >70% stenosis in non-IRAs. For all-cause mortality, the 3 strategies did not differ. For MACE, ischemia-guided PCI was associated with the lowest MACE rate, followed by angiography-guided PCI and medical therapy, which was associated with the highest MACE rate, driven by death and myocardial infarction. Hazard ratios (HRs) for MACE: angiography-guided MV-PCI versus ischemia-guided MV-PCI: HR = 2.23 [95% confidence interval (CI), 1.11–4.48; P = 0.023]; medical therapy versus angiography-guided MV-PCI: HR = 1.58 (95% CI, 0.99–2.63; P = 0.062); medical therapy versus ischemia-guided MV-PCI: HR = 1.72 (95% CI, 1.08–2.74; P = 0.022). Propensity score–adjusted analysis yielded similar results. Conclusions: After primary PCI, complete revascularization in STEMI multivessel disease is associated with lower MACE rates than medical therapy. However, ischemia-testing–guided rather than angiography-guided revascularization was associated with the lowest MACE. This study provides preliminary data and hypotheses for future randomized controlled studies.